STRATEGI PEMBELAJARAN AKUNTANSI DASAR BAGI PESERTA DIDIK SMA NEGERI 2 JAKARTA - Emillia Sastrasasmita; Ruby Ng; Catherine Elliora (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The implementation of economic activities is basically carried out by every human being in their daily lives. These activities include production, distribution and consumption activities. Knowledge of economic concepts, especially accounting, can help everyone to manage personal finances, household budgets to support the economy and social welfare. Some people's perception of accounting as a complicated science occurs because of the complexity of calculations, reporting, analysis and decision making. To overcome this obstacle, an appropriate learning strategy is needed that can encourage the interest and enthusiasm of students. Teachers are required to be more creative and master various ways and strategies to deliver material more interestingly and enjoyably. The methods applied include providing a pre-test before the material is presented and a post-test afterwards. The pre-test and post-test designs are used as a means of evaluation or assessment to ensure the influence and success of learning. The partner, namely senior high school in Jakarta, sees limitations in the current curriculum, namely the delivery of accounting material in schools which has only been introduced starting in grade XII. However, the school hopes that students will be able to participate in various competitions held both at national and international levels, including one in the field of accounting. In addition, the school also can help students prepare in choosing further study paths that can be taken when they graduate from high school later. The output produced is in the form of participation in Seri Seminar Nasional which is held periodically by Tarumanagara University, copyright on HKI and product. ABSTRAK Pelaksanaan kegiatan ekonomi pada dasarnya dilakukan oleh setiap manusia di kesehariannya. Aktivitas ini meliputi kegiatan produksi, distribusi dan konsumsi. Pengetahuan tentang konsep ekonomi khususnya akuntansi, dapat membantu setiap individu untuk mengelola keuangan pribadi, anggaran rumah tangga hingga mendukung perekonomian dan kesejahteraan sosial. Persepsi sebagian orang terhadap akuntansi adalah ilmu yang rumit terjadi karena kompleksitas perhitungan, pelaporan, analisis hingga pengambilan keputusan. Untuk mengatasi kendala ini, diperlukan strategi pembelajaran yang tepat yang dapat mendorong minat dan semangat peserta didik. Tenaga pengajar dituntut lebih kreatif dan menguasai beragam cara maupun strategi untuk menyampaikan materi dengan lebih menarik dan menyenangkan. Metode yang diterapkan antara lain adalah memberikan pre-test sebelum materi dibawakan dan post-test setelahnya. Desain pre-test dan post-test dipakai sebagai cara evaluasi atau penilaian untuk memastikan pengaruh dan keberhasilan pembelajaran. Pihak mitra yaitu salah satu SMA di Jakarta, melihat keterbatasan dalam kurikulum yang berjalan saat ini yaitu penyampaian materi akuntansi di sekolah yang baru diperkenalkan mulai di kelas XII. Namun pihak sekolah berharap para siswa/i mampu mengikuti beragam kompetisi yang diadakan baik di tingkat nasional maupun internasional, termasuk salah satunya di bidang akuntansi. Selain itu juga pihak sekolah berkesempatan untuk membantu kesiapan para siswa/i dalam memilih jalur studi lebih lanjut yang dapat diambil saat lulus SMA nantinya. Luaran yang dihasilkan berupa keikutsertaan pada Seri Seminar Nasional yang diadakan berkala oleh pihak Universitas Tarumanagara, hak cipta pada HKI dan produk.